2015
DOI: 10.1002/cpdd.232
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics, and pharmacodynamics of PD 0348292, an oral, direct factor Xa inhibitor, after single and multiple dosings in healthy subjects

Abstract: The safety, pharmacokinetics, and pharmacodynamics of PD 0348292 were acceptable for future clinical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…26 In a subsequent publication, Xuan et al published the results of three phase I trials on healthy subjects, the first two single ascending-dose studies with randomization to oral eribaxaban (dosage between 2.5-150 mg and 0.1-2.5 mg, respectively) or placebo, while the remaining was a multiple ascending-dose study based on young subjects receiving different dosage of eribaxaban (between 5 and 30 mg) or placebo, along with a cohort of elderly people who instead received 5 mg eribaxaban or placebo. 36 In all studies, a consistent and dose-dependent inhibition (from 4-to 11fold) of thrombin generation was noted, while a modest effect was noted on routine coagulation tests. A single dose was well tolerated in both young and elderly subjects.…”
Section: Eribaxabanmentioning
confidence: 67%
See 1 more Smart Citation
“…26 In a subsequent publication, Xuan et al published the results of three phase I trials on healthy subjects, the first two single ascending-dose studies with randomization to oral eribaxaban (dosage between 2.5-150 mg and 0.1-2.5 mg, respectively) or placebo, while the remaining was a multiple ascending-dose study based on young subjects receiving different dosage of eribaxaban (between 5 and 30 mg) or placebo, along with a cohort of elderly people who instead received 5 mg eribaxaban or placebo. 36 In all studies, a consistent and dose-dependent inhibition (from 4-to 11fold) of thrombin generation was noted, while a modest effect was noted on routine coagulation tests. A single dose was well tolerated in both young and elderly subjects.…”
Section: Eribaxabanmentioning
confidence: 67%
“…35 The peak concentration is usually reached between 3 and 4 hours after administration, while the half-life is approximately 10 hours and nearly 16 to 35% of the drug is excreted with urine. 36 Earlier studies showed that this drug was effective to inhibit arterial thrombosis, with effect comparable to that of aspirin plus clopidogrel. 37,38 Later on, Cohen et al performed a phase II, adaptive dose-ranging study, encompassing the assessment of 100-fold dose range eribaxaban administration in 1,411 patients undergoing total knee replacement.…”
Section: Eribaxabanmentioning
confidence: 99%
“…PD 0348292 is an oral, selective, direct and reversible FXa inhibitor that was safe and well tolerated at a wide range of doses studied in early clinical single‐ and multiple‐dose trials . The pharmacokinetics of PD 0348292 are linear and time‐independent over a dose range of 0.l mg to 10 mg and the terminal half‐life is approximately 10 h. The objectives of this dose‐ranging study were to characterize the dose‐response relationship of PD 0348292 with respect to VTE prevention and bleeding endpoints in subjects undergoing an elective, unilateral TKR and to estimate the dose equivalent to enoxaparin 30 mg bid for efficacy.…”
Section: Introductionmentioning
confidence: 99%